Global agricultural revolutions, trade, policies and vision - Dastagiri, M. B. (Cambridge Scholars Publishing, 2019)
The perceived limits to producing food for a growing global population have been a source of debate and preoccupation for ages. Both experts and the public have been vigilant when regarding the world food situation and outlook. The global agricultural vision has recently moved from eliminating hunger and poverty to a new focus on food security, nutritional security, climate change and economic opportunity. The overall approach can be classified into four strands: food for peace, food for growth, food for the planet, and food for health. This book discusses global agricultural revolutions.